2014
DOI: 10.1016/j.sbspro.2014.09.053
|View full text |Cite|
|
Sign up to set email alerts
|

The Mediating Role of Mobbing on the Relationship between Organizational Silence and Turnover Intention

Abstract: This paper examines the effect of organizational silence and mobbing on turnover intention of 1794 employees, who are employed in 39 different companies. The findings of the study indicate a significant positive effect of both organizational silence and mobbing on employees' turnover intention, besides according to the results there exist a positive significant effect of organizational silence on mobbing. In addition, the findings demonstrate a partial mediation effect of mobbing on organizational silence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
(21 reference statements)
2
13
0
Order By: Relevance
“…Kuvaas (, p. 509) defined employee turnover as “the possibility of employees leaving their job and organization on their own will.” During the last few decades, researchers had immensely focused their investigation on employee turnover due to its evidenced impacts on organizational performance and effectiveness (Bentein, Vandenberghe, Vandenberg, & Stinglhamber, ; Elci, Karabay, Alpkan, & Sener, ; Hong & Chao, ). Because of its impacts, an increasing number of models were presented to accurately predict turnover intention and provide early detection of unanticipated turnover, particularly from high performing employees.…”
Section: Employee Outcomesmentioning
confidence: 99%
“…Kuvaas (, p. 509) defined employee turnover as “the possibility of employees leaving their job and organization on their own will.” During the last few decades, researchers had immensely focused their investigation on employee turnover due to its evidenced impacts on organizational performance and effectiveness (Bentein, Vandenberghe, Vandenberg, & Stinglhamber, ; Elci, Karabay, Alpkan, & Sener, ; Hong & Chao, ). Because of its impacts, an increasing number of models were presented to accurately predict turnover intention and provide early detection of unanticipated turnover, particularly from high performing employees.…”
Section: Employee Outcomesmentioning
confidence: 99%
“…Numerous related studies have described silence as activeness and purposeful behavior. Although the understanding of silence in organizations is initially considered as a sign of loyalty ( 2), but the general pur-Available at: www.ijethics.com pose intentionally refers to the maintenance of negative issues and problems by employees, and in the end it should be said that little research, including (12,(24)(25)(26)(27)(28)(29)(30) deals with the relationship between organizational silence and the desire to leave the job. Therefore, in the end, according to what has been said, it should be note that the third hypothesis is as follows: "Organizational silence has effect on the turnover intention.…”
Section: Organizational Silence and Turnover Intentionmentioning
confidence: 99%
“…It has sometimes been observed that victims and people targeted by pressure tend to increase organizational silence, and this silence reflects their reaction (39). However, limited research (12,40) have examined the effect of exerting pressure on the relationship between organizational silence and the tendency to leave the job. Therefore, in the end, it should be say that the fourth hypothesis is as follows: "Organizational mobbing plays a mediating role in the effect of organizational silence on turnover intention."…”
Section: Organizational Silence and Turnover Intentionmentioning
confidence: 99%
“…Among the studies related to the moderating role of organizational silence, Fernando and Prasad [ 2 ] described the harmful effect of a silencing atmosphere with evidence that the silencing organizational atmosphere, which makes victims unable to reveal their dissatisfaction, prevents the sexual harassment from being expressed outside of the organization. Elçi et al [ 46 ] showed that organizational silence, or the atmosphere that allows harassment, increases employee turnover intention. Jain [ 47 ] investigated factors that cause silence from an aspect of interpersonal relationship and reported that the silence increases when a vertical hierarchical relationship with a supervisor continues.…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%